Executive control development in Tourette syndrome and its role in tic reduction. (April 2018) - Yaniv, Asaf; Benaroya-Milshtein, Noa; Steinberg, Tamar; Ruhrman, Daphna; Apter, Alan; Lavidor, Michal
Abstract: Tourette syndrome (TS) is a childhood-onset disorder characterized by motor and vocal tics. Recent findings point to a possible role of executive functions system development in the tic reduction observed with age. The goal of the present work was to track the development of executive functions system measured by well-established cognitive tasks and its correlation with diminished tic severity over time in order to understand the role of executive functions in the remission process observed in most adults. The first study followed 25 young TS patients, measuring their executive functions and clinical condition at three time- points. In the second study we compared executive functions performance of 19 adult TS patients with 19 healthy controls and 12 remitted TS patients. The first study showed that tic reduction is related to the development of the executive functions components associated with response inhibition. The second study similarly showed impaired inhibition ability in TS patients but not in controls or the remitted TS patients. The remitted group performed at normal or even higher levels on certain measures. We conclude that inhibition, an important executive function, is impaired in subjects suffering from TS and that intact executive function development is related to remission processes. Highlights: TS patients showed impaired inhibition ability, regardless of medication and comorbid conditions. Improvements in some inhibition- dependent measures were accompanied by a significant tic reduction. Remitted TS patients performed normal or even higher levels on certain measures. When the inhibition ability develops properly, patients experience significant clinical improvements as measured by tic reduction.